Complementarity and substitution among industrial incentive schemes - measures targeted to SME versus measures targeted to large projects - Guido Pellegrini; Marusca De Castris (European Regional Science Association (ERSA), 2005)
In Europe several countries adopt different incentives to increase regional development. Some subsidies are targeted to small and medium enterprises, others to large enterprises. Even if the subsidies are targeted to specific industrial aspects, there is a substantial degree of territorial overlapping among them. Usually, every grant scheme operates in isolation, and the evaluation of the different measures does not take into account the presence of complementarity or substitution among them. On the other side, the presence of the SME and large firms in the same area can increase positive externalities and therefore it could be a reason to integrate different grant schemes. The aim of the study is to explore the impact of SME and large project grant scheme in two cases: in areas where financial assistance has been taken up by SME and large firms, and in area where only SME are subsidized. The analysis is based on the two more important measures for local development in Italy: incentives by law 488/92, mainly devoted to SME, and contratti di programma, created for large project. Using data for 784 local labour systems, we estimated the employment effect of subsidies. We control for the presence of spontaneous local growth patterns and for spatial spillovers, using the appropriate spatial models. The preliminary results show that incentives for SME have higher impacts in area where a project financed by contratti di programma is located. This suggests the presence of a relevant level of empirical complementarity between the two incentive measures.
Keywords: 330